2021
DOI: 10.1007/s00784-021-04203-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the protective effects of non-thermal atmospheric plasma on alveolar bone loss in experimental periodontitis

Abstract: Objectives The inhibition of bone destruction is one of the main goals of periodontitis treatment. The aim of this study was to investigate the protective effects of non-thermal atmospheric plasma (NTAP) on alveolar bone loss radiographically, histomorphometrically, and histologically in experimental periodontitis in rats. Materials and methods A total of twenty-eight rats were randomly divided into three groups: control group (CG) (n = 8), periodontitis group (PG) (n = 10), and NTAP group (NTAPG) (n = 10). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…Thus, in an experiment using a periodontitis rat model, the levels of TNF‐α and IL‐1β were reported to be significantly decreased at 7 and 30 days after 2‐min CAP irradiation, while the expression of the anti‐inflammatory cytokine IL‐10, a tissue‐protecting molecule in the periodontal inflammation, was upregulated (Zhang et al, 2018). Similar results were obtained from other periodontitis rat models, whose histological results revealed less infiltration of inflammatory cells in rats treated by argon CAP jet (Kusakcı‐Seker et al, 2021). In a clinical trial, Küçük et al (2020) found that the combined application of SRP and CAP remarkably influenced several clinical markers in patients with periodontitis, wherein CAL was increased but the gingival index and bleeding on probing rate decreased significantly in the CAP‐SRP group compared with the SRP group.…”
Section: Anti‐inflammatory Properties Of Capsupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, in an experiment using a periodontitis rat model, the levels of TNF‐α and IL‐1β were reported to be significantly decreased at 7 and 30 days after 2‐min CAP irradiation, while the expression of the anti‐inflammatory cytokine IL‐10, a tissue‐protecting molecule in the periodontal inflammation, was upregulated (Zhang et al, 2018). Similar results were obtained from other periodontitis rat models, whose histological results revealed less infiltration of inflammatory cells in rats treated by argon CAP jet (Kusakcı‐Seker et al, 2021). In a clinical trial, Küçük et al (2020) found that the combined application of SRP and CAP remarkably influenced several clinical markers in patients with periodontitis, wherein CAL was increased but the gingival index and bleeding on probing rate decreased significantly in the CAP‐SRP group compared with the SRP group.…”
Section: Anti‐inflammatory Properties Of Capsupporting
confidence: 86%
“…In general, rat models are more frequently used due to better operability. In a rat periodontitis model, compared with the control, consecutive CAP irradiation led to less osteoclast infiltration, a lower level of alveolar resorption and cementum damage of infected teeth, and lower expression of OCN and ALP (Kusakcı‐Seker et al, 2021). Nowadays, the therapeutic efficacy of SRP in PD is unsatisfactory due to the complex anatomic structures of the periodontium.…”
Section: Hard Tissue Regeneration Mediated By Cap In Pdmentioning
confidence: 99%
See 1 more Smart Citation